Para além da Lei nº 10.639/2003: da valorização ao reconhecimento da identidade cultural afrobrasileira na rede pública municipal de ensino de Caxias-MA, 2014-2019 - Medeiros, Meiriele de Sousa (Universidade do Vale do Rio dos Sinos, 2022)
When studying African and Afro-Brazilian History and Culture as a thematic axis in Elementary School, possibilities of knowledge of the origins of Afro-Brazilians as active in specific historical and cultural processes are presented, offering them the justification for their valorization, as active in the formation of national society. The present research aimed to analyze the educational practices on Afro-Brazilian and African History and Culture, highlighting how the teaching focused on this theme is being developed in the Elementary School II series of the municipal public network of Caxias-MA, after the implementation of the Law No. 10.639/2003. The elaboration of the research took place, initially, through the bibliographic review of authors who discuss the theme, covering the historiography of Maranhão, the black culture in Maranhão and the school context of education in Caxias. Among the studies that support the research analysis, the following stand out: Botelho (2018), Ferretti (2013), Freire (2000), Moreira (2013), Munanga (2006), Rüsen (2007), among other important authors. Field research was also carried out, through the analysis of the Police Reports of Caxias-MA (2014-2019) and interviews with teachers from the municipal public network of Caxias-MA. The thesis that guided this research is how the data on crimes of racism and racial slur, contained in the police reports of the municipality of Caxias-MA, dialogue with the proposal of a teaching for racial relations and how this relationship is perceived. in institutional documents. When evaluating the interviews, it was found that the teachers are aware of Law nº 10.639/2003 and try to develop the theme through educational and cultural activities, aiming to contribute to the dissemination of ethnicracial relations, even in the face of the challenges encountered, such as an approach that contemplates the multicultural dimensions. The aim of this work is to present new procedures, learning conditions and objectives that induce to rethink ethnic-racial relations, in order to give visibility to teaching practices and inspire educators, making them seek to develop activities aimed at the effectiveness of the everyday school culture of recognition of African civilizational values, as a pedagogical possibility in the construction of knowledge. In this perspective, it is believed that this production will be a collaboration for the construction of education that generates citizenship, which not only meets but also respects and observes with a new look the culture of the black population and relates it to existing educational and inclusive practices, seeking to promote racial equality. Debating this theme will result in the acquisition of a constructive and innovative vision of African and Afro-Brazilian History and Culture for the recognition of the identity of Afro-descendants in the country.
Keywords: História e cultura africana e afro-brasileira; Lei Nº 10.639/2003; Rede Pública Municipal de Caxias – MA; African and afro-brazilian history and culture; Law Nº 10.639/2003; Municipal Public Network of Caxias – MA; ACCNPQ::Ciências Humanas::História